An Intron 7 Polymorphism in APP Affects the Age of Onset of Dementia in Down Syndrome. (12th December 2010) - Jones, Emma L.; Ballard, Clive G.; Prasher, Vee P.; Arno, Matthew; Tyrer, Stephen; Moore, Brian; Hanney, Maria Luisa
Abstract : People with Down syndrome (DS) develop Alzheimer's disease (AD) with an early age of onset. A tetranucleotide repeat, attt5−8, in intron 7 of the amyloid precursor protein has been associated with the age of onset of AD in DS in a preliminary study. The authors examine the impact of this polymorphism in a larger cohort of individuals with DS. Adults with DS were genotyped for attt5−8 and APOE . The results were analysed with respect to the age of onset of dementia. The presence of three copies of the six-repeat allele resulted in onset of dementia seven years earlier than in the presence of other genotypes. Further study is essential to elucidate the mechanism by which this polymorphism functions, with an exciting opportunity to identify novel treatment targets relevant for people with DS and AD.